A Case of Dural Ectasia with Low Back Pain and Sciatica Treated with Integrative Korean Medical Treatment - Oh-Hoon Kwon; Sang-Gyun Kim; Ju-Hun Park; Dong-Hwi Yoo; Ki-Hoon Choi; Ki-Won Choi; Do-Hyung Ha; Hyun-Woo Cho (MEDrang Inc., 2019)
Dural ectasia is defined as ballooning or expansion of the dural sac surrounding the spinal cord. This report describes a rare case of low back pain and sciatica, suspected as being dural ectasia. The patient was hospitalized for 45 days, and underwent integrative Korean medical treatment, including pharmacopuncture, acupuncture, herbal medicine, Chuna therapy, cupping therapy, and physiotherapy. The effect of the treatment was evaluated using the numerical rating scale, Oswestry disability index, European quality of life 5 dimensions, and subjective symptoms. After inpatient treatment, the pain the patient experienced was significantly reduced and the evaluation indices improved. This case report suggested that integrative Korean medical treatment could be an effective therapeutic choice for low back pain and sciatica, with dural ectasia. Further clinical studies are needed to support this observation.